Design of PEI and Amine Modified Metakaolin-Brushite Hybrid Polymeric Composite Materials for CO2 Capturing - Mirkovic, Miljana; Yilmaz, Muge Sari; Kljajevic, Ljiljana; Pavlovic, Vladimir; Ivanovic, Marija; Djukic, Dunja; Eren, Tarik (MDPI, 2023)
In this paper, the properties of organic-inorganic hybrid polymer materials, which were synthesized from an aluminosilicate inorganic matrix with the addition of brushite and aminosilane grafted on one side and PEI covalently bonded composites on the other side, were examined. The synthesized organic-inorganic hybrid polymers were examined in terms of a structural, morphological, thermo-gravimetric, and adsorption-desorption analysis and also as potential CO2 capturers. The structural and phase properties as well as the percentage contents of the crystalline and amorphous phase were determined by the X-ray diffraction method. The higher content of the amorphous phase in the structure of hybrid polymers was proven in metakaolin and metakaolin-brushite hybrid samples with the addition of amino silane and with 1,000,000 PEI in a structure. The DRIFT method showed the main band changes with the addition of an organic phase and inorganic matrix. Microstructural studies with the EDS analysis showed a uniform distribution of organic and inorganic phases in the hybrid geopolymers. The thermo-gravimetric analysis showed that organic compounds are successfully bonded to inorganic polymer matrix, while adsorption-desorption analysis confirmed that the organic phase completely covered the surface of the inorganic matrix. The CO2 adsorption experiments showed that the amine-modified composites have the higher capture capacity, which is 0.685 mmolg (1) for the GM10 sample and 0.581 mmol (1) for the BGM10 sample, with 1,000,000 PEI in the structure.
Keywords: hybrid geopolymers; PEI; XRD; SEM; CO2 capturing; GEOPOLYMERS; ADSORPTION; Polymer Science